IDENTIFIKASI MISKONSEPSI MATERI KESETIMBANGAN KIMIA MENGGUNAKAN TES DIAGNOSTIK PILIHAN GANDA TIGA TINGKAT (THREE-TIER MULTIPLE CHOICE) PADA PESERTA DIDIK KELAS XI MIA SMA NEGERI 2 PEKANBARU - Zaki Dayatul Akbar; Herdini '; Abdullah ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrak: The aim of this research were to know misconceptions and the category level of misconceptions in the second year students of SMA Negeri 2 Pekanbaru aboutt concepts of chemical equallibrium. This research took place in SMA Negeri 2 Pekanbaru and the data were collected on April 2017. was all the students of XI MIA class of four classes. The population consisted of 161 students. The sample was all the population. This research was descriptive quantitative. The technique of collecting data used diagnostic test and interview. The result showed that students found misconception in the definition concept of chemical equallibrium with the percentage was 34,78% (category of average), for the concept of heterogen and homogen was 36,335% (average), the concept of dissociation degree was 33,54% (average), the concept of Kc measurement was 43,785% (average), the concept of Kp measurement was 27,55% (poor), the principle concept of Le Chatelier was 36,764% (average), the concept of using chemical equallibrium in world industry was 23,60% (poor).Key Word : Chemical Equallibrium Misconception, Diagnostic Test,Three-Tier Multiple Choices